New Avenues in Copper-Mediated Trifluoromethylation Reactions Using Fluoroform as the CF3 Source - Yang, Xinkan; Tsui, Gavin Chit (Synlett, 2022)
Organic molecules containing the trifluoromethyl (CF3) group play a vital role in pharmaceuticals, agrochemicals, and materials. New trifluoromethylation methods should encompass capabilities to address issues in efficiency, selectivity, and CF3 source all at once. Fluoroform (CF3H), an industrial byproduct, has emerged as an attractive CF3 source. The reaction profile of the [CuCF3] reagent derived from fluoroform has surpassed its original applications in cross-coupling-type trifluoromethylation. We have discovered a host of unique copper-mediated trifluoromethylation reactions using [CuCF3] from fluoroform, especially under oxidative conditions, to deliver efficient and selective synthesis of trifluoromethylated compounds.1 Introduction2 Construction of C–CF3 Bonds for the Synthesis of Trifluoromethylated Building Blocks2.1 C(sp)–CF3 Bond Formation2.2 C(sp2)–CF3 Bond Formation2.3 C(sp3)–CF3 Bond Formation3 Domino Synthesis of Trifluoromethylated Heterocycles3.1 3-(Trifluoromethyl)indoles3.2 3-(Trifluoromethyl)benzofurans3.3 2-(Trifluoromethyl)indoles4 Trifluoromethylative Difunctionalization of Arynes4.1 Trifluoromethylation–Allylation of Arynes4.2 1,2-Bis(trifluoromethylation) of Arynes5 Pentafluoroethylation of Unactivated Alkenes6 Conclusion
Keywords: trifluoromethylation; fluoroform; copper; heterocycles; arynes